A Hemiclamshell Incision for a Giant Solitary Fibrous Tumor of the Right Hemithorax. (7th November 2012) - Kanlıoğlu Kuman, Nilgün; Şen, Serdar; Çokpınar, Salih; Ceylan, Emel; Tataroğlu, Canten; Boğa, Mehmet
Abstract : A 41-year-old female was admitted with respiratory distress. Chest radiographs showed opacity in the right hemithorax with mediastinal shift. Computed tomography (CT) scan showed a pleural mass with a 22 cm diameter occupying the whole right hemithorax and causing atelectasis. Magnetic resonance imaging (MRI) showed lower position of the right hemidiaphragm and the liver. Superior vena cava and heart were shifted to left. Presence of infiltration to the adjacent tissues could not be clearly evaluated because of pressure effect. Transthoracic needle biopsy specimen was reported to be benign. Because of the size and location of the mass, a hemiclamshell incision was chosen, which allowed excellent visualization and complete dissection of the giant tumor. The histopathology of the resected specimen confirmed solitary fibrous tumor. The patient was stabilized by careful observation and treatment. No complication except pneumonia in the postoperative first month occurred during the 22-month follow-up period.